Trinidad and Religious Pluralism: Sociology and Faith in a Caribbean Island - Ned Rinalducci (Journal of Public and Professional Sociology)
The Caribbean Island of Trinidad has a unique history and demographic makeup causing it to be especially relevant to sociological study. Roughly equal numbers of Trinidadians are of African descent and East Indian descent. I started taking students to the island in 2004 to study the politics of identity, race, ethnicity, religion, and the legacies of colonialism. This piece focuses on exposing undergraduate students to the various religious traditions of Trinidad including Hinduism, Islam, the Orisha faith, and Christianity. Immersion in the rich cultural and religious traditions of Trinidad creates and educational climate and opportunities for teaching and learning like few others places in the world.